Korelasi Tingkat Status Gizi terhadap Tingkat Kebugaran Kardiorespirasi pada Peserta Didik SMP Negeri Surabaya - Tsarwah Mahdiyyah; Junaidi Budi Prihanto (MAN Insan Cendekia Jambi, 2026)
Cardiorespiratory fitness is one of the main components of physical fitness that is important for the body, using Vo2Max as a measurement tool. Cardiorespiratory fitness is influenced by several things such as physical activity, age, and BMI. Nutritional status is used to anticipate excess or deficiency of nutritional status, this is certainly interrelated with cardiorespiratory fitness. This study aims to determine the relationship between nutritional status levels and cardiorespiratory fitness levels in class VIII at SMP Negeri 34 Surabaya. This study uses a quantitative approach with a correlational research design. The population and sample used are students of SMP Negeri 34 Surabaya with a population of 793, which then uses purposive sampling as a data collection technique with a sample size of 85 respondents. The instrument to assess fitness is the PACER test, while the measuring tool for nutritional status is BMI/U. Hypothesis testing uses the Spearman's Rank Order correlation test. The results of implementing the majority of students have a very low level of fitness in cardiorespiratory fitness (82.4%). While the level of nutritional status shows that the majority of nutrition (62.4%) is good. The results of the study, when analyzed using BMI and inverse, indicated a relationship of -0.340 (P-value 0.001), but when using fitness and nutritional status, there was no significance.